Perancangan Sistem Informasi Penjualan pada Perusahaan Jasa Service Provider - Christian, Lianawati; Urfan, Mulfasli (Bina Nusantara University, 2012)
Along with the development of technology, every line of business as well as services needs information systems to support the company operations. This research is objected to analyze, identify information needs, repair and design accounting information system of service sales required by the management to support decision making and address the issues in the running system on a service company. Several methods were carried out on this research, such as data collection and information; analyses on the running system; analyses of research findings;, identification of information needs, and identification of system requirements, as well as object-oriented design methods, namely the problem domain analysis, application domain analysis, architecture design and component diagram. The results obtained in the form of improvements in the running system which was an application that informs the design of document numbering, filing, and reports. The accounting information system of service sales at the studied company produced needed reports timely, completely and accurately that can be utilized by the management in decision-making.